Implications of Green Tea and Its Constituents in the Prevention of Cancer via the Modulation of Cell Signalling Pathway. (21st April 2015) - Rahmani, Arshad H.; Al shabrmi, Fahad M.; Allemailem, Khaled S.; Aly, Salah M.; Khan, Masood A.
Abstract : Green tea is commonly used as a beverage worldwide, especially in China, Japan, Morocco, and Saudi Arabia. Green tea and its constituents have been considered very effective in the prevention and treatment of various diseases. It contains a variety of catechins, which show a pivotal role in the modulation of biological activities and also act as chemopreventive agents. Earlier studies have confirmed that green tea and its chief constituent epigallocatechin gallate (EGCG) have a potential role in the management of cancer through the modulation of cell signaling pathways. In this review, we focused on the beneficial effects of green tea and its constituents in the cancer prevention and treatment and its impact on modulation of molecular pathways.